Pendidikan Wawasan Kebangsaan di Pondok Pesantren Lirboyo dalam Upaya Menangkal Radikalisme - Mahfud, Sahal; Pristiani, Yunita Dwi; Suratman (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2022)
The rise of cases of terrorism and radicalism in the name of Islam in Indonesia is certainly an impetus for all Islamic boarding schools to organize national insight education. The purpose of this study was to determine the understanding of the residents of the Lirboyo Islamic boarding school towards radicalism and national insight education taught at the Lirboyo Islamic boarding school in Kediri. This study uses a qualitative descriptive research method with the subject of Pondok Pesantren Lirboyo Kediri City. This research was carried out by conducting direct observations and interviews with the Management, Mustahik and Santri based on a natural background. The results of this study concluded that the understanding of the residents of the Lirboyo Islamic boarding school to the ideology and actions of radicalism is an ideology and action that deviates and is contrary to the nature of Islam, the nation and state of Indonesia. National Insight Education taught at Lirboyo Islamic Boarding School is through the National Fiqh Takhosus program which is devoted to the Ma'had Aly level and through moral learning. This is intended to be a provision for students and alumni when they return to the community, so that they are able to bring a cool, calm and nationalist spirit to society, and can instill a religious character and spirit, instill the same nature of purpose in seeking knowledge, instill a sense of solidarity, justice, cooperation, and the nature of a sense of loyalty to the agreement (responsibility) and teach simplicity which is a form of fortitude to the wider community.